Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Ekonomi Lokal di UMKM surababaya - Indah, Capriyan Latara; Alfarizi, Rafly; Wahjono , Sentot Imam (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study examines strategies for developing Human Resources (HR) to support local economic growth through the Micro, Small, and Medium Enterprises (MSME) sector in Surabaya. Using a Systematic Literature Review (SLR) method and content analysis techniques, the study identifies the positive impacts of HR development strategies, including socialization and training, digital marketing, and strategic collaboration. The findings indicate that training and socialization contribute to improving managerial and technical skills, while digitalization expands market access for MSMEs and collaboration strengthens business competitiveness. Challenges such as limited technology adoption and restricted access to quality training remain issues requiring further attention. This study recommends enhancing training quality, supporting digital transformation, fostering strategic partnerships, and conducting regular evaluations to promote sustainable HR development, enabling MSMEs to contribute more significantly to the local economy.